2020
DOI: 10.1111/jfbc.13145
|View full text |Cite
|
Sign up to set email alerts
|

Understanding oxidants and antioxidants: Classical team with new players

Abstract: The free radical oxidants such as reactive oxygen species, reactive nitrogen species, and reactive sulfur species are produced inside cells through various metabolic processes. The body is equipped with an antioxidant defense system that guards against oxidative damage caused by these reactive oxidants and plays a major role in protecting cells from oxidative stress and damage. Antioxidants such as glutathione (GSH), thioredoxin, ascorbic acid and enzymes, for example, superoxide dismutase (SOD), glutathione p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
157
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(203 citation statements)
references
References 103 publications
(126 reference statements)
6
157
0
2
Order By: Relevance
“…CAT and SOD, which decompose hydrogen peroxide and superoxide anions, are important in the first defense line of organisms against excess free radicals (Yang et al, 2014). SOD activity correlates well with the immune competence of aquatic organisms because SOD is significant in minimizing the oxidative damage to host cells in immune defenses (Ali et al, 2020). Poniedzialek et al (2015) suggested that the exposure of cylindrospermopsin (CYN) induces a dose-dependent increase in H 2 O 2 concentration in 0.5 h, and when the concentration of H 2 O 2 was highest, the activities of SOD and CAT decreased significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAT and SOD, which decompose hydrogen peroxide and superoxide anions, are important in the first defense line of organisms against excess free radicals (Yang et al, 2014). SOD activity correlates well with the immune competence of aquatic organisms because SOD is significant in minimizing the oxidative damage to host cells in immune defenses (Ali et al, 2020). Poniedzialek et al (2015) suggested that the exposure of cylindrospermopsin (CYN) induces a dose-dependent increase in H 2 O 2 concentration in 0.5 h, and when the concentration of H 2 O 2 was highest, the activities of SOD and CAT decreased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the entire antioxidant protection process, GR can catalyze GSSG to form GSH, and GPX catalysis can help GSH to remove H 2 O 2 from cells. GSH, an important nonenzyme antioxidant substance in cells, can prevent oxidative damage caused by reactive oxidants, can directly or indirectly maintain intracellular oxidative balance, and plays a significant role in protecting cells from oxidative stress (Ali et al, 2020). Rymuszka and Sieroslawska (2018) revealed that in primary leukocytes and small-cell lung cancer cells exposed to nodularin (0.01-0.1 mu g/mL), intracellular ROS production increased significantly and GSH levels decreased.…”
Section: Discussionmentioning
confidence: 99%
“…All cells from bacteria to humans have developed mechanisms to cope with oxidative stress caused by reactive oxygen species (ROS), which are a by-product of respiratory metabolism and cause damage to membranes and DNA [1]. The importance of corresponding signaling pathways that elicit a proper cellular response to ROS accumulation, especially in tumor cells, has been underlined by studies ultimately earning last year's award of the Nobel prize for physiology and medicine (see [2], and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Catalase protects cells from the toxic effects of hydrogen peroxide, and GSR maintains high levels of reduced glutathione in the cell cytoplasm [23]. BLVRA, CRAT, Nampt, and Sorcin are part of metabolic networks.…”
Section: Reactome Analysis In Samples From Hfd-treated Micementioning
confidence: 99%